2014
DOI: 10.4028/www.scientific.net/amm.695.93
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Marine Clay by Biomass Silica (Non-Traditional) Stabilizers

Abstract: The presence of marine clay in Iskandar Malaysia Region, Nusajaya had caused expensive solutions in the construction of structures and roads. Alternatively, soil treatment is suggested to increase the strength of the unsuitable material to meet the constructions requirement for foundation and also to achieve the specifications for development work. In this study, a series of laboratory test has been conducted to determine the potential of Biomass Silica (BS), one of the commercial brands namely “SH-85” to stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 5 publications
3
12
0
Order By: Relevance
“…Therefore, a comparison of the obtained soil parameters for Malacca marine clay with soil parameters of other works has revealed that the Malacca marine clay displays values that are within the range of clay parameters from Johor of Malaysia [30], [34], Kalang (Malaysia) [8], Changi (Singapore) [9], [26], Bangkok (Thailand) [7], Pusan (South Korea) [27], and Yarra Delta (Australia) [6].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, a comparison of the obtained soil parameters for Malacca marine clay with soil parameters of other works has revealed that the Malacca marine clay displays values that are within the range of clay parameters from Johor of Malaysia [30], [34], Kalang (Malaysia) [8], Changi (Singapore) [9], [26], Bangkok (Thailand) [7], Pusan (South Korea) [27], and Yarra Delta (Australia) [6].…”
Section: Discussionmentioning
confidence: 89%
“…Some results have displayed odd values compared to the general tendencies seen for Arkine of Japan [2]- [4], Ashikari (Japan) [35], Oita Prefecture (Malaysia) [2], and Klang (Malaysia) [24]. Nevertheless, the value of liquid limit w LL is found to be not less than 60% [3], [30], [35]; whereas the plastic limit w PL is below 30% [9], [10], [17], [20], [21], [32], [34], [37]. Similarly, the natural water content wn is within the range of liquid limit if not higher [4], [5], [7], [10], [12], [16], [17], [20], [30], [32], [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, they have the potential to contaminate the surrounding geo-environment and nearby groundwater, resulting in limited usage near drinking water sources, despite their merits [92]. Therefore, although recent studies have been conducted on applying sustainable and nontoxic chemicals, such as biomass silica and calcium carbide [89,90], to soil, the economic limitations of applying deep injections to a large-scale site, and the necessity of establishing criteria for the laboratory scale to predict effective in situ performance, should be further researched [91].…”
Section: Chemical Stabilizersmentioning
confidence: 99%
“…Some existing studies pertaining to the use of SH-85 to improve soil properties have been carried out by several researchers on laterite soil [12][13][14], on soft clay [15,16], on marine clay [17,18] and on organic soils [19]. In the research carried out by Latifi et al [12] to improve soil strength, it showed that that 9% of Biomass Silica was the optimum amount of stabilizer for laterite soil, while another study conducted by Marto et al [17] that 12% of Biomass Silica was the optimum amount of stabilizer for marine clay soils. Most of these studies focused on the improvement of soil strength properties, but only two studies focused into the improvement of soil compaction properties, namely Latifi et al [12] and Marto et al [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the research carried out by Latifi et al [12] to improve soil strength, it showed that that 9% of Biomass Silica was the optimum amount of stabilizer for laterite soil, while another study conducted by Marto et al [17] that 12% of Biomass Silica was the optimum amount of stabilizer for marine clay soils. Most of these studies focused on the improvement of soil strength properties, but only two studies focused into the improvement of soil compaction properties, namely Latifi et al [12] and Marto et al [17]. Hence, this study was conducted to focus on the improvement of soil by examining the soil compaction characteristics of Biomass Silica stabilized soil in Kota Kinabalu, Sabah and to compare the results of this study with the findings of the stabilized soils conducted in Peninsular Malaysia.…”
Section: Introductionmentioning
confidence: 99%